The macroeconomic management of increased aid: Policy lessons from recent experience - Shekhar Aiyar; Andrew Berg; Mumtaz Hussain (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper investigates the macroeconomic challenges created by a surge in aid inflows. It develops an analytical framework for examining possible policy responses to increased aid, in terms of absorption and spending of aid - where the central bank controls absorption through monetary policy and the sale of foreign exchange and the fiscal authority controls spending. Different combinations of absorption and spending lead to different macroeconomic consequences. Evidence from five countries that recently experienced an aid surge (Ethiopia, Ghana, Tanzania, Mozambique and Uganda) shows no support for aidrelated real exchange rate appreciation in these countries, but indicates that the fear of Dutch disease played an important part in the policy reaction to aid surges. Fiscal and monetary authorities should coordinate their responses to an aid surge, because an uncoordinated response - typically when fiscal authority wants to spend aid while the central bank wants to avoid exchange rate appreciation - can have serious negative macroeconomic consequences.
Keywords: O11; O23; E52; F35; 330; aid; exchange rate; aid absorption; policy; Entwicklungshilfe; Makroökonomischer Einfluss; Finanzpolitik; Geldpolitik; Afrika